2009
DOI: 10.5860/0700578
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study in Collaboration: Assessing Academic Librarian/Faculty Partnerships

Abstract: Undergraduates attending The George Washington University are required to take courses in the University Writing Program. When it was introduced in 2004, this innovative program institutionalized collaboration between librarians and writing professors. The program was designed to support the university’s strategic goal to enhance challenge, discovery, and quality in student education. Beginning in 2005, instruction librarians crafted a survey to elicit anonymous feedback from their faculty partners to measure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The massive amount of digital information and the complexity of Internet search tools and platforms pose a serious challenge to students as they strive to find reliable evidence from credible sources for their speeches. However, building partnerships with campus and community libraries can teach students how to navigate the world of information and develop responsible practices for conducting academic research (Carpan, 2011;Gaspar & Wetzel, 2009). Library partnerships are important not only for developing speeches during the course, but also serve students' long-term educational goals by enabling them to continue to conduct quality research after the class is over.…”
Section: Best Practice #10: Build Library Partnershipsmentioning
confidence: 99%
“…The massive amount of digital information and the complexity of Internet search tools and platforms pose a serious challenge to students as they strive to find reliable evidence from credible sources for their speeches. However, building partnerships with campus and community libraries can teach students how to navigate the world of information and develop responsible practices for conducting academic research (Carpan, 2011;Gaspar & Wetzel, 2009). Library partnerships are important not only for developing speeches during the course, but also serve students' long-term educational goals by enabling them to continue to conduct quality research after the class is over.…”
Section: Best Practice #10: Build Library Partnershipsmentioning
confidence: 99%
“…The study found that 91% of the librarians questioned think that user education raises the profile of the librarian. Gaspar and Wetzel (2009) carried a case study in collaboration to assess academic librarian/faculty partnerships. The study intended to measure the impact of the library partnership on undergraduate student learning at the George Washington University.…”
Section: Public University Libraries In Jordanmentioning
confidence: 99%